A switchable terahertz device combining ultra-wideband absorption and ultra-wideband complete reflection. Issue 4 (13th January 2022) - Zheng, Zhipeng; Zheng, Ying; Luo, Yao; Yi, Zao; Zhang, Jianguo; Liu, Zhimin; Yang, Wenxing; Yu, Yang; Wu, Xianwen; Wu, Pinghui
Abstract : A metamaterial absorber based on the thermotropic phase change material VO2 has been designed. Flexible switching of absorption performance (bandwidth is 3.3 THz) can be achieved through temperature adjustment. Abstract : Terahertz functional devices have been instrumental in the development of terahertz technology. Moreover, the advent of metamaterials has greatly contributed to the advancement of terahertz devices. However, most of today's metamaterials in the terahertz band exhibit poor performance and are mono-functional. This greatly limits the scalability and application potential of the devices. To achieve diversification and tunability of device functionality, we propose a combination of metamaterial structures and vanadium dioxide film. A metamaterial absorber based on the thermotropic phase change material VO2 has been designed. Flexible switching of absorption performance (complete reflection and ultra-broadband perfect absorption) can be achieved through temperature adjustment. Moreover, the perfectly absorbed bandwidth is a staggering 3.3 THz. The thermal tuning of spectral absorbance has a maximal range of 0.01 to 0.999. The shift in absorption properties is explained by the phase change process of vanadium oxide (MIT). The electric field intensity on the absorber surface at different temperatures was monitored and analysed as a way to correlate the VO2 film phase transition process. The impedance matching theory is applied to explain the high level of absorption generated by the absorber. Finally, the effects of the structural parameters on the performance of the absorber are analysed. This work will have many applications in the terahertz field and offers a wide range of ideas for the design of terahertz-enabled devices.